Ulcerative reflux esophagitis associated with Clostridium ventriculi following hiatoplasty – is antibiotic treatment necessary? A case report - Heidinger, Martin; Gorkiewicz, Gregor; Freisinger, Oana; Brcic, Iva (Zeitschrift für Gastroenterologie, 2020)
Clostridium (C.) ventriculi (known as Sarcina ventriculi) is a ubiquitous gram-positive, anaerobic, acidophilic coccus found in patients with gastric motility disorders. The microorganisms can be identified histologically by their characteristic presentation in tetrads or packets of 8 in hematoxylin and eosin stains. Severe cases of emphysematous gastritis or gastric perforation have been described. Nevertheless, the significance of C. ventriculi in an upper gastrointestinal tract and its pathogenic character remain unclear. We present a 67-year-old woman who underwent hiatoplasty with gastropexy. After 3 months, she underwent a gastroscopy showing gastroesophageal reflux. Biopsies showed ulcerative reflux esophagitis with presence of C.ventriculi, subsequently confirmed by 16S ribosomal RNA gene amplicon sequencing. The barium swallow study revealed an atonic stomach with delayed gastric emptying. The patient was treated with PPI and domperidone. On follow up, 15 months post-operatively, a control gastroscopy showed a stomach with food residues and reflux-associated small erosions. The Clostridium organisms were detected only in oxyntic mucosa biopsies without erosions or ulcerations. We speculate that the recognition of the organisms in the biopsy material is important and suggests dysmotility disorder. However, in our opinion, the presence of C. ventriculi, even in combination with mucosal damage, does not necessarily prompt antibiotic treatment since no complications occurred and inflammation as well as gastric function improved under PPI and prokinetic therapy in our patient. Larger study groups with long-term follow-up are needed to understand whether these organisms could behave as pathogens or are only bystanders in the setting of delayed gastric emptying.
Keywords: esophagitis; Sarcina ventriculi; microbiota; hiatoplasty; Clostridium ventriculi